Bringing Mongolia’s socio-economic environment to German museum visitors: Challenges of the planned Mongolian-German exposition „Steppenwächter” (Guards of the steppe, Dresden 2026) from a museum learning perspective - Vogt, Matthias Theodor (Tudásmenedzsment, 2023)
This text is not an ex-post-analysis, but rather an ex-ante-introduction into some challenges of a planned exposition on the “Mongol Uls” (State of Mongolia) from a museum learning perspective. The Mongolian-German exposition “Dschingis Khan” on the 800th anniversary of the largest empire in the world’s history was a great success with visitors. Therefore, the Mongolian Foreign Minister asked the German Ambassador for a new topic to repeat this success. The Senckenberg Museum Görlitz and the Saxonian Institute of Cultural Infrastructures proposed to thematise the socio-economic environmental challenges of the Mongolian steppe from two perspectives: a natural sciences’ one, and a cultural sciences’ one. The working title is „Steppenwächter––Guards of the Steppe “. Funds provided, we plan to open the exposition September 2026 through January 2027 at Dresden Japanisches Palais; the exposition may then go on tour (including may be Budapest) and finish at Seoul, for to stay at Ulaanbaatar around 2031. Confirmed collaboration will be with Senckenberg Natural History Collections Dresden (SNSD), National Museum of Natural History Ulaanbaatar, Mongolia Cluster of the University of Vienna, and other partners. Mongolian politics and Mongolian (male) society stick extremely to Dshingisism as national ideology. But is this a solution for nowadays immense Mongolian structural problems? Target point of the exposition is the following question: What will the audience do after leaving the exposition? Ideally, her or his task will be to shape the future of the steppe in Mongolia. “Become a steppe guardian! Your ideas might eventually enter into the exposition internet site, to be discussed by a Mongolian-German Youth parliament.”